Preparation, characterization and in vitro digestion of bamboo shoot protein/soybean protein isolate based-oleogels by emulsion-templated approach. (March 2023) - Li, Jiawen; Xi, Yuhang; Wu, Liangru; Zhang, Hui
Abstract: The camellia oil emulsion was stabilized by the bamboo shoot protein and soybean protein isolate complex, and the oleogel system was prepared by the emulsion-templated approach. The results showed that the complex formed a weak gel network through intramolecular and intermolecular hydrogen bonds, and all oleogel samples exhibited good oil binding capacity (>50%). When the ratio of bamboo shoot protein/soybean protein isolate was 4:1, the oleogel exhibited the highest viscosity recovery rate (70.05%) and the strongest cohesiveness (30.98 g). As the ratio of bamboo shoot protein increased, all oleogel samples exhibited elastic-dominated solid-like behavior with good thermal stability. In vitro digestion measurements showed that when the ratio of bamboo shoot protein to soybean protein isolate was 2:1, the maximum release amount of free fatty acids could be reduced to 33.62%, and the release time was extended to 40 min. These results suggest that bamboo shoot protein can be used as a structural agent in oleogels, and it is promising for fabricating oleogel-based products. Graphical abstract: Image 1 Highlights: The emulsion-templated approach was utilized to fabricate oleogels. Bamboo shoot protein/soybean protein isolate complex was applied as the oleogelator. Oleogels formed a weak gel network with good oil holding capacity/thermal stability. Oleogels owned high recovery rate/strong cohesiveness when the protein ratio was 4:1. Oleogels with the ratio of 2:1 exhibited stable release amount/time of fatty acids.